Propriedades vibracionais dos aminoácidos DL-isoleucina e Ácido DL-glutâmico monohidratado e do complexo L-leucina oxalato submetidos a altas pressões - Rêgo, Fellipe dos Santos Campêlo (2019)
Amino acids in L-form are the constituents of all living beings. In crystalline state their structure is stabilized mainly by hydrogen bonds and they can present two enantiomers (L and D) and a racemic (DL) form. The amount of papers dealing on DL form of amino acid has increased in the last years, but it is still fewer than that on L-form. Although L and DL for being formed essentially by the same molecule the way they are linked can provide very different properties. In this way high pressure Raman spectroscopy is an useful tool that can be used to study the role of hydrogen bonds in the structure that compose amino acids as well as compare the behavior of its counterparts. In this report we present a detailed analysis of the vibrational properties of crystals of DL-isoleucine, DL-glutamic acid monohidrate and L-Leucine oxalate. These compounds were grown by slow evaporation of the solvent at room temperature. Its vibrational properties were studied at room temperature and at high hydrostatic pressure through Raman spectroscopy. For the sample of DL-isoleucine at ambient conditions, the mode assignment was done in terms of the potential energy distribution (PED) through density functional theory calculations. Both nitrogen and neon were used as pressure transmitting media. The pressure-dependent investigation shows modifications in the Raman spectra recorded between 30 cm-1 and 3200 cm-1 that were interpreted as phase transitions undergone by the crystal between 1.3 GPa and 1.9 GPa and between 3.6 GPa and 5.1 GPa. Finally, the stress was simulated on the unit cell of the crystal from ambient pressure to 5.0 GPa. The sample of DL-glutamic acid monohydrate, the modes assignment were made by comparison with works made in L-forms ( and ) glutamic acid and other amino acids. Neon gas was used as pressure transmitting media. In the investigation under high pressures were found three structural phase transitions. The first one at about 0,9 GPa, the second one at about 4.8 GPa showed conformations involving , and the water molecules, while the third one involved various parts of glutamic acid, as well as the water molecules. The crystal of DL-glutamic acid monohydrate demonstrate similar stability compared with its polymorphs -L-glutamic acid and -L-glutamic acid (for the first phase transition). However, phase II of DL-glutamic acid monohydrate demonstrated highest structural stability. Water molecules seem to play important role in this structural stability. In addition, all transitions were reversible. The sample of L-Leucine oxalate, the assignment of the modes has also been made by comparison with literature. Neon gas was used as pressure transmitting media. The results of the experiments under high pressures showed that this sample undergoes two phase transitions at high pressure, the first one between 0.9 GPa and 1.0 GPa and the second one between 2.6 GPa and 3.1 GPa both characterized by the appearance and disappearance of bands related to lattice modes with regard to internal modes. The crystal of L-Leucine oxalate was more stable than your constituent L-Leucine and less stable than oxalic acid. Decompression experiments revealed that the phase transitions observed in the three samples are reversible.